Gaya Belajar Siswa: Apakah Ada Hubungannya dengan Hasil Belajar Siswa? - Harmila Adhani; Nurhasanah Nurhasanah; Muhammad Tahir; Itsna Oktavianty (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The purpose of the study was to describe whether or not there was a relationship between a student's learning style and a student's IPS learning outcomes. This research was conducted in SDN Cluster 4 Selaparang Subdistrict consisting of 3 elementary schools, namely SDN 33 Mataram, SDN 34 Mataram, and SDN 24 Mataram. The type of research used in this study is correlational research. The population in this study was students of class V SDN Cluster 4 Selaparang Subdistrict as many as 119 students. A sample number of 54 students were obtained with the Simple Random Sampling technique. Data collection techniques through questionnaires and documentation. The instruments in this study took the form of questionnaires or questionnaires compiled on the Likert Scale. Data analysis techniques using correlation analysis. The results showed that there was a positive and significant relationship between students' learning styles (visual, audio, kinesthetic) and IPS learning outcomes. The large coefficient of correlation between a student's learning style (visual, audio, kinesthetic) and IPS learning outcomes is 0.605 and falls into a strong category. This shows that 36.6% of IPS learning outcomes are influenced by students' learning styles, while the remaining 63.4% are influenced by other factors such as learning motivation, parental parenting, and learning environment. and falls into a strong category. This shows that 36.6% of IPS learning outcomes are influenced by students' learning styles, while the remaining 63.4% are influenced by other factors such as learning motivation, parental parenting, and learning environment. and falls into a strong category. This shows that 36.6% of IPS learning outcomes are influenced by students' learning styles, while the remaining 63.4% are influenced by other factors such as learning motivation, parental parenting, and the learning environment